The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/economies9040191
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Evidence on Factors Conditioning the Turning Point of the Public Debt–Growth Relationship

Abstract: This paper contributes to the limited literature on the factors conditioning the turning point of the public debt–growth relationship. A decade after the global financial crisis, when the debt ratio in many countries was still above pre-crisis levels, the COVID-19 pandemic again increased the pressure on public finances. It revived the debate on the ability to promote economic recovery through debt-financed government expenditure. However, more intense government borrowing increases its costs and uncertainty a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…In general, only a few main reasons can be singled out, due to which a decrease in the level of public debt in the country can be observed. These are direct debt repayment due to an increase in revenues and decrease in budget expenditures, growth of inflation rate, which leads to depreciation of debt denominated in the respective currency, and rapid economic growth, which increases the level of GDP, and thus reduces the ratio of debt to this value (Butkus et al, 2021). Thus, when assessing the trends related to the reduction of public debt, it is worth assessing the causes of this phenomenon as well.…”
Section: Resultsmentioning
confidence: 99%
“…In general, only a few main reasons can be singled out, due to which a decrease in the level of public debt in the country can be observed. These are direct debt repayment due to an increase in revenues and decrease in budget expenditures, growth of inflation rate, which leads to depreciation of debt denominated in the respective currency, and rapid economic growth, which increases the level of GDP, and thus reduces the ratio of debt to this value (Butkus et al, 2021). Thus, when assessing the trends related to the reduction of public debt, it is worth assessing the causes of this phenomenon as well.…”
Section: Resultsmentioning
confidence: 99%
“…These were years characterised by scarcity, rationing, and patriotic self-restraint appeals, which led to an abnormally high rate of savings at a time when government budget deficits were huge. Butkus et al (2021a;2021b) found that an increase in public debt to GDP ratio is more likely to result in a positive debt effect on private consumption and investment. A positive relationship between public debt and private consumption and economic growth was found in China by Gu et al (2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the author found that the negative impact of debt on economic growth occurs when the debt reaches 60 per cent of GDP. Meanwhile, researchers Butkus et al (2021a) analyzing the breaking point of the relationship between public debt and growth, in terms of the tax burden, identify that low taxes (below the threshold level of 16.5 per cent of GDP tax revenue) are related to positive but insignificant effect of debt on economic growth. Leão (2015) found that very high public debt will not result a high tax burden or default because the central bank can keep government bond yields as low as necessary to make debt servicing negligible.…”
Section: Literature Reviewmentioning
confidence: 99%